GAMBARAN PELAKSANAAN INISIASI MENYUSUI DINI (IMD) - Safrina; Tengku Sri Wahyuni (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
The World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) have recommended that children start breastfeeding within the first hour after birth and be exclusively breastfed for the first six months of life (no food or other fluids are given). , including water) (UNICEF & WHO, 2018). An estimated 78 million babies - or three in five babies - are not breastfed in the first hour of life. This puts them at a higher risk of death and disease and makes them less likely to continue breastfeeding (World Health Organization, 2018a). Data from WHO shows that only 40% of infants have received early initiation of breastfeeding (IMD). WHO itself targets that by 2030 70% of infants have received early initiation of breastfeeding (WHO & UNICEF, 2018). The type of research used is descriptive, namely research that clearly describes the variables studied without doing statistical tests. This research was conducted at BPM Pematangsiantar City. The study was conducted in March 2021 with a sample size of 29 people. The sampling method in this study was non-probability sampling, namely by consecutive sampling. The description of the IMD implementation shows that the majority of respondents are aged 20-35 years (65.5%) and the least is <20 years old (6.9), the highest parity is 3 (34.5%) and the least parity is 5 (6.9%). ), all respondents gave birth at term pregnancy (100%), and all respondents did early initiation of breastfeeding (100%) while the implementation of IMD was mostly carried out immediately after birth (89.7%) and the longest IMD implementation was between 30 minutes to 30 minutes. d 1 hour (69%) but there are also those who carry out IMD less than 30 minutes (10.3%). Type of Research Analytical survey with cross sectional design. It is hoped that health workers will carry out an IMD in every delivery immediately after the baby is born and the need for husband and family support in accompanying the delivery process in carrying out IMD.